Mechanically durable memristor arrays based on a discrete structure design - Wang, Ting (2022)
Memristors constitute a promising functional component for information storage and in-memory computing in flexible and stretchable electronics including wearable devices, prosthetics, and soft robotics. Despite tremendous efforts made to adapt conventional rigid memristors to flexible and stretchable scenarios, stretchable and mechanical-damage-endurable memristors, which are critical for maintaining reliable functions under unexpected mechanical attack, have never been achieved. Here, the development of stretchable memristors with mechanical damage endurance based on a discrete structure design is reported. The memristors possess large stretchability (40%) and excellent deformability (half-fold), and retain stable performances under dynamic stretching and releasing. It is shown that the memristors maintain reliable functions and preserve information after extreme mechanical damage, including puncture (up to 100 times) and serious tearing situations (fully diagonally cut). The structural strategy offers new opportunities for next-generation stretchable memristors with mechanical damage endurance, which is vital to achieve reliable functions for flexible and stretchable electronics even in extreme and highly dynamic environments.